Validity of SQ-FFQ with FR 24 hour for measuring macro nutrient and total flavonoid dietary intake in reproductive age women with obesity - Nina Indriyani Nasruddin (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2022)
Background: Obesity has become a global epidemic with a threefold increase in cases since 1975. Dietary restriction that contains high calories, fat and also dietary interventions with natural bioactive foods such as flavonoids can prevent obesity. Assessment of intake for dietary regulation can use the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) and 24-hour Food Recall (FR) method Purposes: This study aimed to determine the average intake of macronutrients and total flavonoids using the SQ-FFQ and FR 24 Hr methods in women of childbearing age (WUS) with obesity and to knew the differences and correlations between the methods. Methods: a cross-sectional design was carried out from May to June 2021 in Kendari City. Samples were obtained through the purposive sampling technique as many as 30 WUS aged 18-49 years with a body mass index (BMI) ≥ 25 kg/m2. Data were collected through interviews to obtain information on macronutrient intake and total flavonoids using the SQ-FFQ and 24-hour FR questionnaire instruments. Anthropometric data was performed to assess nutritional status. The data were analyzed using the SPSS program through different tests and correlation tests. Results: The mean intake of macronutrients (energy, protein, fat, and carbohydrates) and total flavonoids using the SQ-FFQ method was higher than the 24-hour FR method. The different tests of the intake of energy, protein, carbohydrates, and total flavonoids using the SQ-FFQ method was significantly different from the 24-hour FR method (p<0.001). Fat intake was not significantly different between the two methods (p=0,267). The intake of energy, protein, fat, carbohydrates, and total flavonoids correlated by the two methods (p<0.05) with a correlation coefficient (r) of energy intake = 0.538, protein = 0.556, fat = 0.395, carbohydrates 0.665, and total flavonoids = 0.723. Conclusion: We conclude that The SQ-FFQ method is a valid tool to measure the intake of energy, protein, carbohydrates, fat and total flavonoids in obese women in women with obesity in the city of Kendari, Southeast Sulawesi, Indonesia.